1990
DOI: 10.1104/pp.93.4.1552
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Synthesis and Release of nod-Gene-Inducing Flavonoids from Alfalfa Roots

Abstract: Flavonoid signals from alfalfa (Medicago sativa L.) induce transcription of nodulation (nod) genes in Rhizobium meliloti. Alfalfa roots release three major nod-gene inducers: 4',7-dihydroxyflavanone, 4',7-dihydroxyflavone, and 4,4'-dihydroxy-2'-methoxychalcone. The objective of the present study was to define temporal relationships between synthesis and exudation for those flavonoids. Requirements for concurrent flavonoid biosynthesis were assessed by treating roots of intact alfalfa seedlings with [U-14C]-L-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 21 publications
4
39
1
1
Order By: Relevance
“…4; Table II). In contrast, 5-deoxyflavonoids (flavone numbering system) from alfalfa root exudate (17,18) did not promote growth ofR. meliloti (Tables I and IV) promote polysaccharide formation by rhizobia (3), that phenomenon did not have major effects on A600 data in these experiments.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…4; Table II). In contrast, 5-deoxyflavonoids (flavone numbering system) from alfalfa root exudate (17,18) did not promote growth ofR. meliloti (Tables I and IV) promote polysaccharide formation by rhizobia (3), that phenomenon did not have major effects on A600 data in these experiments.…”
Section: Discussionmentioning
confidence: 67%
“…Culture and Treatment of Organisms 'Moapa 69' alfalfa (Medicago sativa) seeds were imbibed and rinsed with water to collect seed exudate as described previously (10 (10,17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the concentration of formononetin increases when an AM fungus was present in the rhizosphere, even in P-fertilized plants that were not yet colonized by the fungus (Volpin & Kapulnik, 1994), This implies that formononetin production in the roots is induced merely by the presence of the fungus in the host rhizosphere, or by appressoria formation, but that visible colonization of the tissue is not required, Formononetin has not been shown to have antimicrobial activities, but is a precursor of the isoflavonoid phytoalexins produced in alfalfa in response to stresses and microbial infections (Dalkin et al, 1990a), Formononetin is usually not found in exudates of young (8-d-old) alfalfa roots, but is secreted from stressed roots (Maxwell & Phillips, 1990) and is produced in leaves of alfalfa inoculated with Ascockyta imperfecti (Olah & Sherwood, 1971), Formononetin precursors (2',4,4'-trihydroxychalcone, 4',7-dihydroxyflavanone and daidzein) and medicarpin precursors (2'-hydroxyformononetin and vestitone) were all below detectable levels (Volpin et aL, 1995), However, in well-colonized roots, 20-35 d after germination, the concentrations of two other isoflavonoids, genistein and biochanin A, were both elevated. This response might be specific to the G. intraradices-Medicago sativa interaction, Harbison & Dixon (1993) reported elevated amounts of medicarpin, medicarpinmalonylglucoside, daidzein, coumestrol, formononetin, formononetin-malonylglucoside and 4',7-dihydroxyBavone in roots of M. truncatula 7^0 d after Glomus inoculation, but HPLC profiles of the uninoculated M. truncatula roots were also very different from those obtained from M. sativa.…”
Section: Induction Of Defence Responsesmentioning
confidence: 99%
“…It has been known for nearly a century that root exudates-the chemicals released from root systems into the soil-have profound effects on microorganisms in the rhizosphere (for review, see Curl and Truelove, 1986;Rovira, 1991). In recent years, specific sugars and phenolic compounds from plant exudates have been shown to induce microbial genes required for pathogenesis and symbiosis (Rossen et al, 1985;Stachel et al, 1985;Shearman et al, 1986;Peters and Long, 1988), and the cellular sources of such chemicals are now being examined (Maxwell and Phillips, 1990;Graham, 1991;Oommen et al, 1994;McKhann et al, 1997).…”
mentioning
confidence: 99%